2011
DOI: 10.5336/medsci.2010-20018
|View full text |Cite
|
Sign up to set email alerts
|

Breast Conserving Surgery and Modified Radical Mastectomy in Turkish Women with Breast Cancer: A Prospective Analysis of Quality of Life

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Kli ni ği miz de me me ko ru yu cu cer ra hi (MKC) ve son ra sın da rad yo te ra pi uy gu la nan has ta lar ile modi fi ye ra di kal mas tek to mi (MRM) uy gu la nan has ta la rın ame li yat son ra sı ya şam ka li te le ri ni kar şı laş tır mak. G Ge e r re eç ç v ve e Y Yö ön n t te em m l le er r: : Ça lış ma ya kli ni ği miz de Ocak 2006 ile Ocak 2008 ta rih le ri ara sın da me me kan se ri ta nı sı ile ame liyat edi len has ta lar alın mış tır. Ne o ad ju van ke mo te ra pi ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
3
0
5
Order By: Relevance
“…In a similar study, body image, future perspective, arm symptoms and hair loss was worse in patients who received MRM while there was no difference in systemic therapy side effects and breast symptoms between BCS and MRM groups (Akca, 2011). Kement et al (2011) reported better quality of life both physically and mentally in patients who received BCS. In similar studies comparing BCS and MRM, Han et al (2010) showed higher physical and mental status in BCS patients while Arndt et al (2008) reported better physical and social functioning and general quality of life.…”
Section: Discussionmentioning
confidence: 94%
“…In a similar study, body image, future perspective, arm symptoms and hair loss was worse in patients who received MRM while there was no difference in systemic therapy side effects and breast symptoms between BCS and MRM groups (Akca, 2011). Kement et al (2011) reported better quality of life both physically and mentally in patients who received BCS. In similar studies comparing BCS and MRM, Han et al (2010) showed higher physical and mental status in BCS patients while Arndt et al (2008) reported better physical and social functioning and general quality of life.…”
Section: Discussionmentioning
confidence: 94%
“…23 Yapılan bazı çalış-malarda, 35 yaş ve altındaki meme kanseri olgularında, MKC'nin mastektomi uygulanan olgulara göre lokal nüks açısından dezavantajlı olduğu belirtilse de, 40 yaş altındaki erken evre meme kanTurkiye Klinikleri J Med Sci 2013;33 (1) …”
Section: Discussionunclassified
“…Halsted tarafından 1890'lı yıllardan itibaren popülarize edilen radikal mastektomi, geçtiğimiz yüzyıl uzunca bir süre meme kanseri tedavisinde standart olarak kabul edilmiştir [4]. Fakat morbiditesi olduk-ça yüksek bir ameliyat yöntemi olan radikal mastektomi ile lokal kontrol sağlanabilir olmasına rağmen hastaların belli bir kısmı bir süre sonra meydana çıkan metastatik lezyonlar sonrasında kaybedilmiştir [5]. Bunun sebebi daha sonraları kabul görmeye başlayan meme kanserinin sistematik bir hastalık olduğu gerçeğine dayandırılmıştır [5].…”
Section: Discussionunclassified
“…Fakat morbiditesi olduk-ça yüksek bir ameliyat yöntemi olan radikal mastektomi ile lokal kontrol sağlanabilir olmasına rağmen hastaların belli bir kısmı bir süre sonra meydana çıkan metastatik lezyonlar sonrasında kaybedilmiştir [5]. Bunun sebebi daha sonraları kabul görmeye başlayan meme kanserinin sistematik bir hastalık olduğu gerçeğine dayandırılmıştır [5].…”
Section: Discussionunclassified
See 1 more Smart Citation